(untitled) (Medical Forum Monthly, 2024)
Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the department of surgery & radiology, Pak Red Crescent Teaching Hospital, affiliated with Pak Red Crescent Medical & Dental College, Lahore from July 2016 to June 2018. Materials and Methods: A total of 600 patients irrespective of age and sex were included in this by consecutive nonprobability sampling technique. All subjects were screened for Anti-HCV antibody by immune-chromatographic strip-test method. An equal number of patients with and without HCV infection were chosen in two different groups. Group I was seronegative and Group II was seropositive patients. Ultrasound scan of abdomen was performed on all the patients to see especially for gallstones. Data was collected for age, sex, presence or absence of gallstones, on a specially designed performa. Data was analyzed using SPSS version 21. Descriptive statistics & Chi-square test was used. Results: Out of 600 patients, 414 (69%) were females and 186 (31%) were males. Mean age of the patients was 38 ± 1.28 years. Youngest patient was 17 years old and eldest was 90 years old. Males and females with Hepatitis C antibodies were 121 (40.33%) and 179 (59.66%) respectively. In Group II patients suffering from HCV infection had a significantly high frequency of gallstones (25.66%) as compared to HCV seronegative Group I (8.66%). P-value was significant (p=0.01). Conclusion: There is a strong association of gallstone disease in patients suffering from HCV infection.